Enhanced photoelectrochemical activity by nanostructured V2O5/TiO2 bilayer - Mumtaz, A. (American Institute of Physics Inc., 2016)
Hydrogen production by splitting of water using solar means is a renewable alternative and is a need of the hour. The generation of hydrogen is studied using nanostructured V2O5/TiO2 bilayer photoctatalyst synthesized by two different methods. The solution deposition followed by annealing and flame oxidized methods are applied to deposit the nanostructured V2O5 onto TiO2 nanorod arrays. These two methods are compared and studied using X-ray diffraction, field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), electron energy loss spectrum and photoelectrochemical study. The morphological study provides the optimized surface area of the TiO2 nanorod arrays. It shows that 0.45 mL tetra butyl titanate at 180C shows the improved surface area. It also differentiates the 3D network as morphology of nanostructured V2O5/TiO2 bilayer photoctatalyst synthesized by flame oxidation method. Electron energy loss spectrum confirms the presence of respective elemental states of V2O5/TiO2 bilayer photoctatalyst. Photoelectrochemical studies show the photocurrent density of 7.89Î¼A/cm2 at 0 V vs Ag/AgCl using flame oxidized nanostructured V2O5/TiO2 nanorod arrays. This study explores the potential of flame oxidized synthesis of nanostructured photocatalysts. Â© 2016 Author(s).